Assessment of the unsteady performance of a turbocharger radial turbine under pulsating flow conditions: Parametric study and modeling. (August 2022) - Mosca, Roberto; Mihaescu, Mihai
Abstract: A characteristic of radial turbines for turbocharger applications subject to pulsating flow is the deviation of the turbine performance compared with corresponding continuous flow conditions, typically associated with gas-stand experiments. The performance deviations under pulsating flow generate a hysteresis loop that encloses the performance line obtained in gas-stand conditions and their intensity is demonstrated to grow with increasing pulse amplitude and frequency. Predicting the performance deviations is of great interest to improve the predictive capabilities of reduced-order models and enhance engine-turbocharger matching. In this work, the performance response of a turbocharger radial turbine is studied with respect to variations of the normalized pulse amplitude (between 0.4 and 1.6 ) and the pulse frequency (between 20 Hz and 100 Hz ). Results show that the hysteresis loop expands with increasing pulse amplitude and frequency, so that the turbine cannot be treated as a quasi-steady device. The characteristic trends of the turbine performance are also highlighted with respect to pulse amplitude and frequency variations. The expansion ratio is registered to improve by + 4.0 % with increasing pulse amplitude and decrease by - 1.3 % with increasing pulse frequency. An opposite trend is otherwise registered for the isentropic efficiency, which decreases by - 6.5 % for increasing pulse amplitude and increases by + 6.5 % for increasing pulse frequency. Finally, through a simple model, the deviations of the turbine performance from quasi-steady to pulsating flow conditions are demonstrated to depend on the time derivative of the pressure pulse and the residence time of the fluid particle rather than pulse amplitude and frequency.